Validation of SymGrid-services framework through event-based simulation. (10th May 2011) - Carstea, Alexandru; Frincu, Marc; Macariu, Georgiana; Petcu, Dana
In response to the need of the symbolic computing community to develop a collaborative environment that exploits the capabilities of multiple symbolic computing software tools, we designed and implemented recently the SymGrid-services solution based on web and grid technologies. This paper describes its validation platform and simulation environment in which a SymGrid-services' user can test various scheduling algorithms. The discrete event simulation approach is tailored to the behaviour and the life cycle of workflows comprising interdependent tasks for symbolic computations. The test results show the robustness of the SymGrid-services framework.